2011
DOI: 10.4045/tidsskr.10.1441
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamolforgiftninger etter innføring av ny salgsordning

Abstract: There is no evidence that the number of paracetamol poisonings or deaths has increased since the place of sale restriction was lifted. The proportion of patients with liver toxicity/liver damage, and the number of patients evaluated for liver transplantation may be increasing. However, the development in paracetamol poisoning should be monitored in the coming years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…Paracetamol caused in average about six deaths annually in the study period (Table 2). Although the death rate of paracetamol poisonings is low in Norway compared to other European countries, [24] the death rate has more than doubled from the 1990s. [25] But our study also found six annual deaths in the three last study years from NSAIDs, a group of analgesics normally associated with low risk of acute mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Paracetamol caused in average about six deaths annually in the study period (Table 2). Although the death rate of paracetamol poisonings is low in Norway compared to other European countries, [24] the death rate has more than doubled from the 1990s. [25] But our study also found six annual deaths in the three last study years from NSAIDs, a group of analgesics normally associated with low risk of acute mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Forskjellen kan indikere en økning, men kan like gjerne skyldes ulik vektlegging av agens når vi identifiserte (10,11). Undersøkelser Giftinformasjonen har foretatt viser at antall henvendelser til Giftinformasjonen vedrørende inntak av store doser paracetamol har økt betydelig de siste årene, men at antall paracetamolrelaterte sykehusinnleggelser og dødsfall har vaert relativt stabilt (12). Oversiktene over agens (tabell 2 og 3) er interessante fordi dette er informasjon som er vanskelig å få fra andre kilder.…”
Section: Resultaterunclassified
“…I en norsk studie fant man at antall henvendelser til Giftinformasjonen om paracetamolforgiftning økte betydelig etter innføringen av LUA-ordningen i 2003, men at dette ikke førte til flere sykehusinnleggelser på grunn av paracetamol og heller ikke til flere paracetamoldødsfall. Forfatterne kunne likevel ikke utelukke økt antall alvorlige paracetamolforgiftninger (5).…”
Section: Situasjonen I Norgeunclassified